Surface quality control of thin SiN layer by optical measurements - Gierowski, Jakub; Pawłowska, Sandra (Photonics Letters of Poland, 2021)
Fiber optic interferometers have a wide range of applications including biological and chemical measurements. Nevertheless, in case of a reflective interferometer setup, standard silver mirrors cannot be used in every measurement, due to their chemical activity. In this work, we investigate the surface quality of a thin optical layer of silicon nitride (SiN) which can serve as an alternative material for silver mirrors. We present measurements carried out with a Fabry-Perot fiber optic interferometer working in a reflective mode. Measurement results allow us to determine the surface quality of the investigated layer. Full Text: PDF References K. Karpienko, M.S. Wróbel, M. Jedrzejewska-Szczerska, "Determination of refractive index dispersion using fiber-optic low-coherence Fabry-Perot interferometer: implementation and validation", Opt Express, 53, 077103 (2014). CrossRef Jedrzejewska-Szczerska M., Gnyba M., Kosmowski B. B. "Low-coherence fibre-optic interferometric sensors", Acta Phys. Pol. A 120, 621 (2011). CrossRef M. Jedrzejewska-Szczerska "Response of a new low-coherence Fabry-Perot sensor to hematocrit levels in human blood",Sensors 14(4), 6965 (2014). CrossRef M. Kosowska, D. Majchrowicz, K.J. Sankaran, M. Ficek, K. Haenen, M. Szczerska, "Doped Nanocrystalline Diamond Films as Reflective Layers for Fiber-Optic Sensors of Refractive Index of Liquids", Materials 12, 2124 (2019). CrossRef Shou-YiChang, Yi-Chung Huang, "Analyses of interface adhesion between porous SiO2 low-k film and SiC/SiN layers by nanoindentation and nanoscratch tests", Microelectron. Eng. 84(2), 319 (2007). CrossRef X. Wang, C. Wang, X. Shen, F. Sun, "Potential Material for Fabricating Optical Mirrors: Polished Diamond Coated Silicon Carbide". Appl. Opt. 56, 4113 (2017). CrossRef G. Coppola, P. Ferraro, M. Iodice, S. De Nicola, "Method for measuring the refractive index and the thickness of transparent plates with a lateral-shear, wavelength-scanning interferometer", Appl. Opt. 42, 3882 (2003). CrossRef H. Mäckel, R. Lüdemann, "Detailed study of the composition of hydrogenated SiNx layers for high-quality silicon surface passivation", J. Appl, Phys. 92, 2602 (2002). CrossRef N. Atman, M. Krzywinski, "Visualizing samples with box plots", Nat. Methods, 11(2), 119 (2014). CrossRef M. Vignesh, R. Balaji, "Data analysis using Box and Whisker Plot for Lung Cancer", International Conference on Innovations in Power and Advanced Computing Technologies,(2017). CrossRef